Uso de ácidos graxos omega-3 na prática clínica e sua influência na resposta inflamatória em pacientes com neoplasia colorretal e indicação cirúrgica: uma revisão integrativa - Garnes, Sergio Dos Anjos [UNIFESP] (2020)
Inflammation is a physiological response triggered by injury, whether infectious or not. In recent decades, this process has become a hallmark of cancer since it is a critical component for tumor progression and metastasis. Omega-3 fatty acids has been shown to be a potent anti- inflammatory agent and its application in clinical practice mainly in colorectal cancer has shown relevants results. This study aimed to conduct an integrative review on the use of omega- 3 in patients with colorectal neoplasia undergoing surgical treatment. The related articles on the topic were organized chronologically, thus showing the evolution of knowledge and its application in clinical practice. The results of clinical trials were analyzed using omega-3 in the perioperative period, with special attention to the type of composition, dose offered, route of administration, period and time of use and the impact on the modulation of the inflammatory process of patients being treated. The results after this analysis can help decision making for the better management of these patients, in addition to providing new strategies for the development of future research regarding the proof and improvement of the effectiveness of omega-3 in the perioperative inflammatory control of patients with colorectal neoplasia.